Advocating for the Preservation of Senior Housing: A Coalition at Work Amid Gentrification in Detroit, Michigan. Issue 2 (4th March 2021) - Perry, Tam; Berglund, Lisa; Mah, Julie; Sanford, Claudia; Schaeffer, Pamela; Villeneuve, Evan W.
ABSTRACT: As cities become increasingly gentrified, the experiences of their oldest and longest residents often go underrecognized in favor of class-based and racialized concerns about displacement. Underrepresented in both scholarship and organizing efforts, eviction and displacement pose unique threats to seniors because of the link between their health and housing needs. To uncover possible strategies for coalition building and senior housing policy advocacy in quickly changing neighborhoods, this article examines the strategic efforts of Senior Housing Preservation-Detroit (SHP-D). Originally formed in 2013 to address the displacement of a single building of seniors, SHP-D aims to raise awareness of and advocate to preserve housing in a city whose core is rapidly changing. In this article, we offer an overview of the coalition's advocacy as a way to highlight the role of community mobilization toward preserving affordable senior housing. We outline (a) the formation of the coalition, (b) recent developments, (c) strategic planning processes, and (d) lessons learned by this coalition that may be useful for other senior housing advocacy efforts. We conclude by addressing SHP-D's attention to immediate health needs of older adults in congregate housing due to the COVID-19 pandemic.